Primeros ensayos de inducción de embriones somáticos de Quercus suber L. - Bueno, A. J.; Manzanera, M. A. (Scientia gerundensis, 1992)
Susceptibility of cork oak (Quercus suber L.) embryos, endosperm and ovules to somatic embryogenesis induction has been studied. 2,4-D at different concentrations was tested. Samples were collected every two weeks, dong the fruit development period, from June till September. The embryos formed callus, from which globular and heart and torpedo-shaped structures and somatic embryos at different developing degrees were obtained.
Keywords: Cork oak; Quercus suber; Somatic embryogenesis; tissue culture; vegetative propagation